PERFORMANCE EVALUATION OF ASPHALT CONCRETE WEARING COURSE (ACWC) MIXTURE USING RECLAIMED ASPHALT PAVEMENT (RAP) WITH PALM OIL BUNCHES BIOASPHALT REJUVENATOR - Taufik, Ramdhan
This study aims to analyze and evaluate the characteristics of AC-WC mixtures containing Reclaimed Asphalt Pavement (RAP) material using Palm Oil Bunches Bioasphalt rejuvenator, Reclaimed Asphalt Pavement (RAP) material content using Palm Oil Bunches Bioasphalt rejuvenator on the Resilient Modulus using the UMATTA tool, and Reclaimed Asphalt Pavement (RAP) material content using Palm Oil Bunch Bioasphalt rejuvenator against Fatigue with indirect tensile fatigue test method with a Dynamic Testing System tool. The asphalt used in the research was Pen 60/70. The asphalt needs to be tested for its basic properties. The aggregate gradation used for the asphalt mixture is asphalt concrete wearing course (AC-WC) gradation based on the General Specifications for Bina Marga 2018 Revision 2. This research uses three variations of are asphalt concrete wearing course (AC-WC) mixture with a RAP composition of 15%, 20%, and 25% to the total weight of the mixture as well as the addition of Bioasphalt 23% to the weight of RAP asphalt as a rejuvenator and asphalt concrete wearing course (AC-WC) with a composition of 100% new material as a mixture control. Optimum Asphalt Content by conducting Marshall testing to obtain results from stability, flow and Marshall Quotient testing, as well as volumetric mixtures in the form of Voids between Mineral Aggregate (VMA), Voids in the Mixture (VIM) and Voids Filled with Asphalt (VFA). Next, further testing was carried out consisting of resilience modulus testing using the Indirect Tensile Test method using the Universal Material Apparatus (UMATTA) which refers to AASHTO TP-31 and ASTM D 4132-82 using temperature variations of 25°C and 45°C and fatigue testing which was carried out using the Indirect Tensile Fatigue Test Method at a temperature of 25°C with three levels of controlled stress loading method of 250 KPa, 300 KPa and 400 Kpa based on all tests carried out guided by BS EN 12697- 24:3.23. The Optimum Asphalt Content values in the AC–WC mixture using a high RAP mixture results in the need for less new asphalt, this is due to the asphalt content in the RAP. The resilient modulus value of mixed variations at the test temperature of 25°C was greater than at 45°C, indicating that temperature greatly influences the properties and resilient modulus value. Apart from that, the resilient modulus value increases when the mixture contains RAP material, this is because RAP can increase the stiffness and role of Palm Oil Bunches Bioasphalt as a rejuvenator for aging materials. In fatigue testing, the 25% RAP mixture has a shorter fatigue life than the 20% RAP mixture. Based on the resilient modulus test, it shows that the 25% RAP mixture has a high stiffness of 1.29 compared to the 20% RAP mixture, this shows high stiffness but lower fatigue resistance compared to 20% RAP mixture. From laboratory test results, it was concluded that the AC-WC mixture containing 20% RAP plus Palm Oil Bunches Bioasphalt rejuvenator had the highest fatigue resistance performance due to repeated loads (fatigue).